Предмет: Алгебра,
автор: oksimini
решите уравнение (х-2)(х^2+8х+16)=7(х+4)
Ответы
Автор ответа:
0
(x - 2) (x + 4)^2 = 7(x+4)
(x - 2)*(x + 4)^2 - 7(x+4) = 0
(x+ 4) ((x - 2)(x + 4) - 7) = 0
(x+ 4) (x^2 + 2x - 8 - 7) = 0
(x + 4) ( x^2 + 2x - 15) = 0
x + 4 = 0
x1 = - 4
x^2 + 2x - 15 = 0
D = 4 + 4*15 = 64
x2 = ( - 2 + 8)/2 = 6/2 = 3;
x3 = ( - 2 - 8)/2 = - 10/2 = - 5
Ответ:
- 5; - 4; 3
(x - 2)*(x + 4)^2 - 7(x+4) = 0
(x+ 4) ((x - 2)(x + 4) - 7) = 0
(x+ 4) (x^2 + 2x - 8 - 7) = 0
(x + 4) ( x^2 + 2x - 15) = 0
x + 4 = 0
x1 = - 4
x^2 + 2x - 15 = 0
D = 4 + 4*15 = 64
x2 = ( - 2 + 8)/2 = 6/2 = 3;
x3 = ( - 2 - 8)/2 = - 10/2 = - 5
Ответ:
- 5; - 4; 3
Автор ответа:
0
Спасибо огромное все доступно и понятно!!!))))
Автор ответа:
0
Не забудь отметить как лучшее)
Похожие вопросы
Предмет: Геометрия,
автор: kss770
Предмет: Математика,
автор: abylkasymabai
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Алгебра,
автор: vaNOrma